Vegetation resistance and resilience to a decade‐long dry period in the temperate grasslands in China. Issue 15 (5th July 2021) - Liang, Minqi; Cao, Ruochen; Di, Kai; Han, Daorui; Hu, Zhongmin
Abstract: The duration of climate anomalies has been increasing across the globe, leading to ecosystem function loss. Thus, we need to understand the responses of the ecosystem to long‐term climate anomalies. It remains unclear how ecosystem resistance and resilience respond to long‐term climate anomalies, for example, continuous dry years at a regional scale. Taking the opportunity of a 13‐year dry period in the temperate grasslands in northern China, we quantified the resistance and resilience of the grassland in response to this periodic dry period. We found vegetation resistance to the dry period increased with mean annual precipitation (MAP), while resilience increased at first until at MAP of 250 mm and then decreased slightly. No trade‐off between resistance and resilience was detected when MAP < 250 mm. Our results highlight that xeric ecosystems are most vulnerable to the long‐term dry period. Given expected increases in drought severity and duration in the coming decades, our findings may be helpful to identify vulnerable ecosystems in the world for the purpose of adaptation. Abstract : Resistance and resilience of grasslands to a decade‐long dry climate was investigated. Resistance increased with mean annual precipitation (MAP), while resilience increased until at MAP of 250 mm and then decreased slightly. No trade‐off between resistance and resilience was found in xeric grasslands.